2019
DOI: 10.1103/physrevd.99.024012
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic string and black hole limits of toroidal Vlasov bodies in general relativity

Abstract: We numerically investigate limits of a two-parameter family of stationary solutions to the Einstein-Vlasov system. The solutions are toroidal and have non-vanishing angular momentum. As one tunes to more relativistic solutions (measured for example by an increasing redshift) there exists a sequence of solutions which approaches the extreme Kerr black hole family. Solutions with angular momentum larger than the square of the mass are also investigated, and in the relativistic limit the near-field geometry of su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…In the axially symmetric case the situation is different. The numerical methods that have been used in previous works [2,3,46,47] rely on an iteration procedure which must converge in order to produce a solution. Such iterative methods have also been employed in the spherically symmetric setting, where it is observed that convergence is only achieved for a certain range of the parameters.…”
Section: Comparison Of Numerical Methods In the Spherically Symmetric...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the axially symmetric case the situation is different. The numerical methods that have been used in previous works [2,3,46,47] rely on an iteration procedure which must converge in order to produce a solution. Such iterative methods have also been employed in the spherically symmetric setting, where it is observed that convergence is only achieved for a certain range of the parameters.…”
Section: Comparison Of Numerical Methods In the Spherically Symmetric...mentioning
confidence: 99%
“…Here K is a positive constant, which we call the amplitude, and Φ is a given function. In principle the amplitude could be incorporated into Φ but since it plays an important role in the numerical fixed point methods used in [2,3,46,47] we separate it out. The quantities E and L z are given by…”
Section: The Axisymmetric Einstein-vlasov Systemmentioning
confidence: 99%
“…In [4] these configurations are modeled by a one-particle distribution function (DF) depending only on the energy E, azimuthal L z and total angular momentum L of the particles. Examples are given in which the DF is described by a generalized polytropic ansatz [5,6] depending only on E and L z . In this article, we provide additional examples where the DF is a function of E and the inclination angle i defined by cos i = L z /L.…”
Section: Introductionmentioning
confidence: 99%
“…Several simplifications and generalizations have since then been obtained, and we refer to [22] for a simplified and general approach, to [6] for the existence of highly relativistic static solutions and to [11] for the existence of stationary solutions in the axisymmetric case. There are several other existence results and also results about the properties of the static solutions in the literature, and we refer to [8] for a review and to [2,3,9] for more recent results.…”
Section: Introductionmentioning
confidence: 99%